?DETERMINATION OF HEAVY AND TOXIC METALS Zn, Cd, Pb AND Cu IN VEGETABLES BY VOLTAMETRY (Biological Sciences - PJSIR, 1994)
A simple and reliable voltametric procedure has been developed for trace metal analysis in vegetables. Different varieties of vegetables were analyzed for the contents of Zn.Cd, Pb and Cu and results are reported. Comparison between different vegetables showed that leafy vegetables have higher concentrations of metals as compared to other vegetables. Peels of vegetables have higher contents of metals. Distribution patterns of metals in soil, stem and leaves of vegetables are discussed.